Generasi muda dan tanggung jawab sosial terhadap pendidikan masyarakat - Hanifah, Huriyyatusy (Maliki Interdisciplinary Journal, 2025)
Youth are among the most valuable assets of a nation, as they play a vital role in shaping the future, particularly in the field of education. Education is not only about improving individual abilities but also serves as the foundation for building a stronger and more advanced society. For this reason, young people are expected to take social responsibility by actively contributing to the improvement and expansion of educational access for all. Their contribution is not limited to being recipients of education but extends to becoming agents of change who bring forward new ideas, social initiatives, and innovations relevant to current developments. Practical involvement can be seen in literacy programs in remote areas, tutoring for underprivileged children, and the use of technology to create effective learning media. Such efforts help overcome limitations in educational resources, raise public awareness of the importance of education, and support equal opportunities for learning. At the same time, active participation in education also shapes the character of young people. Through direct engagement, they develop empathy, social responsibility, and leadership skills that are valuable for society as a whole. These experiences serve as an important foundation for building a fair, inclusive, and competitive community in the global era. In conclusion, the social responsibility of youth in education is not only a moral obligation but also a key factor in preparing a smarter, stronger, and future-ready society.